Homogenization of monotone problems with uncertain coefficients - Francu, Jan; Nechvatal, Ludek (Mathematical Modelling and Analysis, 2011)
The homogenization problem for a nonlinear elliptic equation modelling some physical phenomena set in a periodically heterogeneous medium is studied. Contrary to the usual approach, the coefficients in the equation are supposed to be uncertain functions from a given set of admissible data satisfying suitable monotonicity and continuity conditions. The problem with uncertainties is treated by means of the worst scenario method.